SERENITY, SUSTAINABILITY DAN SPIRITUALITY DALAM INDUSTRI MANAJEMEN WISATA RELIGI - Aun Falestien Faletehan (Jurnal Pariwisata, 2019)
By using a phenomenology study in two cases: Tiban Mosque Turen Malang and the Tomb of Sunan Ampel Surabaya, this research was designed to answer three questions: (1) How are the values of 'Serenity, Sustainability and Spirituality' embodied in religious tourism?; (2) How could managers design a tourism strategy to generate the values of 'Serenity, Sustainability and Spirituality'?; and (3) How is the model of religious tourism management based on the values of 'Serenity, Sustainability and Spirituality'?. As a part of qualitative approach, this research used data collection techniques such as interviews, observation and documentation. The results of this study demonstrated that the value of serenity was indicated by peacefulness in mind, feelings and body; the value of sustainability was marked with the environmental, social and economic aspects; and spirituality was specified by connectedness with oneself, the environment and the Transcendent. Related to these values, the managers seem succeeded in designing tourism strategies through strategic planning, asset organizing system, travel guides and evaluation method. This process leads to the emergence of the model of religious tourism management based on the values of 'Serenity, Sustainability and Spirituality'.